2012
DOI: 10.1123/jsm.26.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Toward Team or Player? How Trust, Vicarious Achievement Motive, and Identification Affect Fan Loyalty

Abstract: This study extends literature on the effects of fan identification on fan loyalty, and antecedents that trigger such effects. This study incorporates trust, a key relationship marketing construct, in the sport industry. The relationship between trust and two other critical antecedents of sport fan loyalty, identification and vicarious achievement motive, is examined from the perspectives of both fan-player and fan-team. The results show that antecedents from distinct perspectives influence loyalty differently.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 67 publications
8
86
0
Order By: Relevance
“…This is, in part, because the positive attributions associated with the team are not limited to other team members but can instead extend to objects that represent the team (Branscombe & Wann, 1991). This is because, in part, objects are often strong representations of the values, norms, and beliefs associated with teams (Wu et al, 2012). These objects are branded with logos, colors, or images that invoke strong emotional bonds derived from identification (Smith, Graetz, & Westerbeek, 2008).…”
Section: Team Identification and Emotional Attachmentmentioning
confidence: 99%
“…This is, in part, because the positive attributions associated with the team are not limited to other team members but can instead extend to objects that represent the team (Branscombe & Wann, 1991). This is because, in part, objects are often strong representations of the values, norms, and beliefs associated with teams (Wu et al, 2012). These objects are branded with logos, colors, or images that invoke strong emotional bonds derived from identification (Smith, Graetz, & Westerbeek, 2008).…”
Section: Team Identification and Emotional Attachmentmentioning
confidence: 99%
“…For example, Trail et al (2005) found that role identity (TII) was correlated (r = .396) with conative loyalty (measured by four items: likelihood of attending future games, purchasing the team's merchandise, buying the team's clothing and supporting the team), whereas found that role identity (TII; β = .33) predicted the probability of purchase intention (3 items: attend another sporting event, buying additional products, and spending more than 50% of the fan's spectator sport budget on the team). Wu et al (2012) explained 25% of repatronage intentions (attending games, watching games on TV, and purchasing merchandise) and Shapiro et al (2013) found 19.4% shared variance in a single item of attendance intentions and role identity (TII). Based on these results, we propose the following hypothesis:…”
Section: Role Identity and Conative Loyaltymentioning
confidence: 99%
“…Within sport consumer behavior literature, the importance of role identity as a fan of a particular team (called team identification when using the TII historically) has been shown to be related to behavioral intentions relative to a team (conative loyalty), explaining anywhere from 10.9% of the variance to 25% of the variance (Wu et al, 2012;Yoshida et al, 2015). However, not all measures of conative loyalty were the same.…”
Section: Role Identity and Conative Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Torlak et al (2014) investigated the relationship among the identification level of the supporters with the football clubs, quality perception toward the licenced products of the clubs and purchasing intentions, and determined that identification level was more effective on purchasing intention than it was on quality perception of the supporters. On the other hand, Wu et al (2012) seperated identification in two parts which were identification as a fan-team level and identification as a fan-player level and determined that team identification was the major determinant of fans' loyalty intentions, however, player identification had an indirect effect on fans' loyalty intentions. In addition, Stevens and Rosenberger (2012) determined that fan identification, following sport and involvement positively influenced fan loyalty.…”
Section: Iiiiii Identification-brand Loyalty Relationship In Footballmentioning
confidence: 99%